Brown adipose tissue activation as measured by infrared thermography by mild anticipatory psychological stress in lean healthy females. Issue 4 (18th February 2016) - Robinson, Lindsay J.; Law, James M.; Symonds, Michael E.; Budge, Helen
Abstract : New Findings: What is the central question of this study? Does psychological stress, which is known to promote cortisol secretion, simultaneously activate brown adipose tissue function in healthy adult females? What is the main finding and its importance? One explanation for the pronounced differences in brown adipose tissue function between individuals lies in their responsiveness to psychological stress and, as such, should be taken into account when examining its in vivo stimulation. Brown adipose tissue (BAT) has been implicated in the pathogenesis of obesity, type 2 diabetes and the metabolic syndrome and is a potential therapeutic target. Brown adipose tissue can have a significant impact on energy balance and glucose homeostasis through the action of uncoupling protein 1, dissipating chemical energy as heat following neuroendocrine stimulation. We hypothesized that psychological stress, which is known to promote cortisol secretion, would simultaneously activate BAT at thermoneutrality. Brown adipose tissue activity was measured using infrared thermography to determine changes in the temperature of the skin overlying supraclavicular BAT ( T SCR ). A mild psychological stress was induced in five healthy, lean, female, Caucasian volunteers using a short mental arithmetic (MA) test. The T SCR was compared with a repeated assessment, in which the MA test was replaced with a period of relaxation. Although MA did not elicit an acute stress response, anticipation of MA testing led to an increase in salivary cortisol, indicative of an anticipatory stress response, that was associated with a trend towards higher absolute and relative T SCR . A positive correlation between T SCR and cortisol was found during the anticipatory phase, a relationship that was enhanced by increased cortisol linked to MA. Our findings suggest that subtle changes in the level of psychological stress can stimulate BAT, findings that may account for the high variability and inconsistency in reported BAT prevalence and activity measured by other modalities. Consistent assessment of this uniquely metabolic tissue is fundamental to the discovery of potential therapeutic strategies against metabolic disease. Abstract :